THE EFFECT OF CORPORATE GOVERNANCE AND CORPORATE CULTURE ON FIRM MARKET VALUE TO IMPROVE FINANCIAL PERFORMANCE - Fathiyah, Fathiyah; Mufidah, Mufidah (Dinasti International Journal of Digital Business Management, 2020)
The purpose of this research is to analyze the effect of corporate governance and corporate culture on firm market value to improve financial performance. Corporate governance is measured by audit committee,boards of directors, board meeting and nomination . Corporate culture is measured by Corporate culture promotion While financial company performance is measured by return on assets. This research was conducted on companies listed on the Indonesia Stock exchange on indexed LQ 45 for period of 2016-2018. The sample was selected for 25 companies. The method of analysis uses associate descriptive analysis with path analysis. Based on the results of the study found that corporate governance and culture promotion indirectly effect on financial performance with firm market value as intervening variable.